2019
DOI: 10.1021/acsnano.9b00302
|View full text |Cite
|
Sign up to set email alerts
|

Chiral 2D Perovskites with a High Degree of Circularly Polarized Photoluminescence

Abstract: Chiral materials are of particular interest and have a wide range of potential applications in life science, material science, spintronic, and optoelectronic devices. Two-dimensional (2D) hybrid organic–inorganic lead halide perovskites have attracted increasing attention. Incorporating the chiral organic ligands into the layered lead iodide frameworks would introduce strong chirality in pure 2D perovskites for potential applications in circularly polarized light (CPL) emission and detection; nonetheless, stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
519
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 406 publications
(546 citation statements)
references
References 58 publications
24
519
3
Order By: Relevance
“…In addition to 3D cubic perovskite we just mentioned, 2D perovskite is another perovskite family that possesses good polarization property because of its asymmetric layered crystal structure. For example, Ghoshal et al demonstrated a high DOLP of 0.73 from an individual (BA) 2 PbI 4 NW,43 and Ma et al reported polarized PL based on a group of chiral (MBA) 2 PbI 4 microplates with a DOLP of 0.176 44. Compared with perovskite‐based devices in the literature, the printed perovskite NW arrays in this study present the highest DOLP of 0.84, suggesting its potential for polarized light application.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to 3D cubic perovskite we just mentioned, 2D perovskite is another perovskite family that possesses good polarization property because of its asymmetric layered crystal structure. For example, Ghoshal et al demonstrated a high DOLP of 0.73 from an individual (BA) 2 PbI 4 NW,43 and Ma et al reported polarized PL based on a group of chiral (MBA) 2 PbI 4 microplates with a DOLP of 0.176 44. Compared with perovskite‐based devices in the literature, the printed perovskite NW arrays in this study present the highest DOLP of 0.84, suggesting its potential for polarized light application.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with reduced‐dimensional perovskites, 2D perovskite films possess the merit of stronger chirality for the large mole fraction of organic chains, which exactly benefits for optoelectronic and spintronic devices. Very recently, needle‐shaped pure chiral ( R‐/S ‐MBA) 2 PbI 4 2D perovskites ( Figure a,b) have been reported to achieved a huge degree of the circularly polarized photoluminescence ( P value) of 17.6% (Figure c), which is much larger than that of RDCPs . In particular, with the increase of temperature, the chirality transfer reduces and the spin flip increases, resulting in the decrease of P value (Figure d).…”
Section: Properties Of Chiral Perovskite Materialsmentioning
confidence: 98%
“…c) Statistical histogram of the degree of circularly polarized PL |P| for ( R‐ and S‐ MBA) 2 PbI 4 excited by a 473 nm laser at 77 K. d) Degree of circularly polarized PL ( P ) as a function of temperature of two microplates for each type chiral 2D perovskites. Reproduced with permission . Copyright 2019, American Chemical Society.…”
Section: Properties Of Chiral Perovskite Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to their 3D counterparts, the emerging 2D Ruddlesden–Popper perovskites have received increasing attention due to their better ambient stability . Up to now, 2D Ruddlesden–Popper perovskites have been demonstrated to exhibit abundant and adjustable optoelectronic properties, high quantum efficiency, and large specific surface area . Furthermore, the synthetic routes of layered perovskites which depend on self‐assemble with low cost and efforts are facial and economically .…”
mentioning
confidence: 99%